Factors Associated with Cigaret Smoking in Elementary School Children - West, Malcolm (1983)
A survey of 625 elementary school children in an urban area for substance use, specifically, cigarets, alcohol and drugs, and the social factors associated with such use, revealed 38 admitted smokers in this age range, strongly influenced by parents, siblings and peers who smoked. Cigaret use was also associated with drug and alcohol use. These findings corroborate those from studies of teenagers who smoke, showing that peer pressure is not the sole factor in starting to smoke, as several other studies have claimed. In elementary school children, smoking is rare enough to be considered an early indicator of social deviation.